Solidarity Beyond Borders: SEAblings and Digital Activism in Southeast Asia - Muhammad Fikri (proceedings.icesy, 2026)
The development of social media opens up new space for the formation of digital solidarity that transcends geographical and national boundaries. The SEAblings phenomenon represents a practice of cross-border solidarity in Southeast Asia that developed through the interaction of X social media users in late August to early September 2025. This research aims to examine how SEAblings' cross-border digital solidarity is constructed through interaction and culture, from a Social Identity Theory perspective. This study applies a netnographic method with a qualitative approach, using secondary data in the form of uploads and public interactions of social media users X relevant to the SEAblings phenomenon. The analysis is carried out interpretively to understand the process of interaction and the formation of a collective digital culture. The results show that SEAblings' digital activism, initiated by Yammi (@singhyam), the main actor, gradually forms through social categorization, identification, and comparison. Interaction based on texts, symbols, and narratives of togetherness encourages the transformation of empathy into tangible collective action. These findings confirm the consistency of Social Identity Theory in explaining cross-border digital solidarity and the role of social media in the construction of empathy-based identity and solidarity.